2019
DOI: 10.19136/era.a7n1.2195
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico y evaluación del uso y aprovechamiento del agua en el Distrito de Riego 05-Delicias, Chihuahua, México

Abstract: ME (2020) Diagnóstico y evaluación del uso y aprovechamiento del agua en el Dis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the DR-05 district, areas under perennial crops have been increasing year after year, resulting in greater pressure on the availability of water and its sustainable management. It was also concluded that the increase in crops with a high consumption of water has increased pressure on the management of this resource and on decision making, since they represent the crops with the highest water consumption per unit area [46].…”
Section: Discussionmentioning
confidence: 99%
“…In the DR-05 district, areas under perennial crops have been increasing year after year, resulting in greater pressure on the availability of water and its sustainable management. It was also concluded that the increase in crops with a high consumption of water has increased pressure on the management of this resource and on decision making, since they represent the crops with the highest water consumption per unit area [46].…”
Section: Discussionmentioning
confidence: 99%